Efficacy of PEGylated ciliary neurotrophic factor superagonist variant in diet-induced obesity mice - Battista, Maria Rosaria; Grigoletto, Antonella; Tedeschini, Tommaso; Cellucci, Antonella; Colaceci, Fabrizio; Laufer, Ralph; Pasut, Gianfranco; Di Marco, Annalise (PLOS ONE, 2022)
Ciliary neurotrophic factor (CNTF) is a neurotrophic cytokine able to induce appetite reduction, weight loss and antidiabetic effects. However, its susceptibility to neutralizing anti-CNTF antibodies in patients hampered its use for treatment of human obesity and diabetes. In addition, CNTF has a very short plasma half-life, which limits its use as a therapeutic agent. Solutions, directed to prolong its in vivo effects, vary from the implantation of encapsulated secreting cells to identification of more active variants or chemical modification of the protein itself. PEGylation is a widely used modification for shielding proteins from circulating antibodies and for increasing their plasma half-life. Here, we have selected DH-CNTF, a CNTF variant which has a 40-fold higher affinity for the CNTF receptor α accompanied by an increased activity in cellular assays. The PEGylated DH-CNTF retained the biological activity of native protein in vitro and showed a significant improvement of pharmacokinetic parameters. In an acute model of glucose tolerance, the PEG-DH-CNTF was able to reduce the glycemia in diet-induced obese animals, with a performance equaled by a 10-fold higher dose of DH-CNTF. In addition, the PEGylated DH-CNTF analog demonstrated a more potent weight loss effect than the unmodified protein, opening to the use of CNTF as weight reducing agent with treatment regimens that can better meet patient compliance thanks to reduced dosing schedules.